The many assassinations of Samir, the seller of dreams - Nayeri, Daniel (Levine Querido, 2023)
"From award-winning author Daniel Nayeri comes a mesmerizing adventure set along the enchanting silk road, where caravans of merchants carried spices, perfumes, furs, and in the case of one swindler named Samir, nothing but dreams. The story begins with a young orphan running for his life. Lucky for him he runs into Samir, a portly huckster whose silver tongue saves the boy. Samir names him Monkey, and claims him as his new servant. But Monkey, a strict and devout soul, is horrified to discover that his new master is a liar whose dealings have angered every village he's ever passed through. The villagers have hired a collection of murderers, including a Viking berserker, a Rogue legion, a Persian mystic, a Bedouin clan, a Mongolian gunner, a Chinese ablutionist, and if that wasn't enough, the most terrifying killer of all, a mythic figure only known as "Cid." With rich illustrations throughout, here is an epic tapestry and buddy comedy all at once, a heartfelt tale of what makes a family, the expansive nature of love, and the precise market value of a good story." --
Keywords: Abenteuer; Betrüger; Mörder; Waisenkind; Seidenstraße; Silk Road / Juvenile fiction; Adventure stories; Assassins / Juvenile fiction; Swindlers and swindling / Juvenile fiction; Route de la soie / Romans, nouvelles, etc. pour la jeunesse; JUVENILE FICTION / General; Asia / Silk Road / https://id.oclc.org/worldcat/entity/E39PBJj8JTKRmWPGXFqt87Vpyd; Action and adventure fiction; Kinderbuch